KAJIAN HUKUM TERHADAP PRAKTEK PENERAPAN UNDANGUNDANG NO. 35 TAHUN 2014 TENTANG PERUBAHAN ATAS UNDANG-UNDANG NO. 23 TAHUN 2002 TENTANG PERLINDUNGAN ANAK (Studi Terhadap Putusan No. : 201/Pid.Sus/2016/PN Skt.). - MURTIYANI, MURTIYANI (Dinamika Hukum, 2017)
The purpose of this study is to assess the implementation of the Act 35 of2014, especially in the Decision No .: 201 / Pid.Sus / 2016 / PN Skt in theperspective of the Criminal Procedure Code.Background of this research that is now common cases involvingchildren as victims. This requires the public to be wary of her son in conductingsurveillance. Likewise for law enforcement agencies should continue to improvein taking action so that every child victim cases that can be resolved soon in orderto maintain the trust of community. Act of Law No. 23 of 2002 on ChildProtection was amended by Act 35 of 2014 including with a view to moreeffective law enforcement.The study was conducted with the approach of legislation and caseapproach. The research material consists of primary legal materials in the form ofa law on Protection of Children and its amendments, the law of criminalprocedure and secondary legal material in the form of the judge's decision. Inaddition, tertiary legal materials are dictionaries and dictionary Indonesian law.Data analysis was carried out by juridical qualitative.The results showed that in terms of the law of criminal procedure, thejudge's ruling in Decision No. : 201 / Pid.Sus / 2016 / PN Skt. has fulfilled therequirements of Article 197 Jo.Article 194 of Criminal Procedure CodeKeywords: Application of Act 35 of 2014 concerning changes in Act 23 of 2002on Child Protection, Decision No. : 201 / Pid.Sus / 2016 / PN